Liraglutide: The Latest Addition to Armamentarium of Antidiabetic Drugs - Dubey, AK; Biswas, NR (Health Renaissance, 2011)
DOI: 10.3126/hren.v8i2.4424 Health Renaissance, May-Aug 2010; Vol 8 (No.2):117-121